2022
DOI: 10.1021/acs.macromol.1c02631
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Poly(vinylpyridine)-Containing Brush Block Copolymers: Combined Synthesis of Grafting-Through and Grafting-to Approaches

Abstract: Synthesis of brush block copolymers (brush BCPs) enables the generation of BCPs with various block compositions and chain architectures, which determine the morphologies and functionalities of the polymeric materials. Here, we report a synthetic strategy for preparing structurally diverse brush BCPs via combined synthesis of the grafting-through and grafting-to approach. The polystyrene-based brush copolymer with an azide functionality is synthesized by sequential ring-opening metathesis polymerization of norb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The morphological analysis of the grafted filler is highly essential as there is the possibility of formation of self-assembled nanostructures. , The grafted fillers themselves can form highly hierarchical nanostructures due to the inherent nature of the selected block copolymer to self-assemble into different morphologies. In our previous studies, it was observed that the same block copolymer was capable of forming different morphologies like spherical micelle, caterpillar-like, and gigantic octopus in the polymer matrix .…”
Section: Resultsmentioning
confidence: 99%
“…The morphological analysis of the grafted filler is highly essential as there is the possibility of formation of self-assembled nanostructures. , The grafted fillers themselves can form highly hierarchical nanostructures due to the inherent nature of the selected block copolymer to self-assemble into different morphologies. In our previous studies, it was observed that the same block copolymer was capable of forming different morphologies like spherical micelle, caterpillar-like, and gigantic octopus in the polymer matrix .…”
Section: Resultsmentioning
confidence: 99%
“…Significant improvement in the synthetic capability is required, as a number of difficulties are observed in synthesizing bottlebrush polymers containing PVPs via ring-opening metathesis polymerization, a popular approach for synthesizing ultrahigh molecular weight polymers. 174,175 In addition to the synthetic advances, new segment chemistry in combination with the PVP block would also diversify the scope of multicompartment particles.…”
Section: Discussionmentioning
confidence: 99%
“…Different from random coil linear BCPs, bottlebrush block copolymers (BBCPs) show highly stretched molecular conformations due to large steric repulsions among densely grafted polymer side chains. [ 5,28‐49 ] Consequently, polymer chain entanglements are greatly reduced relative to their linear analogues. This enables rapid self‐assembly of high‐MW BBCPs ( M w > 1.0 MDa) into ordered one dimensional (1D) photonic structures which can reflect visible structural colors.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Therefore, amphiphilic BBCPs were designed and synthesized for directed self‐assembly of inorganic nanocrystals by using strong hydrogen bonding, forming organic/inorganic hybrid materials with greatly enhanced contrast of dielectric constant. [ 36,46‐49 ] As a result, reflectivity greatly increased when compared to neat polymer materials. Typically, solution‐casting method has been used to prepare coating films via slow evaporation‐induced self‐assembly on planar surfaces such as on glass slides, which is challenging for real applications such as on a curved surface of a car.…”
Section: Background and Originality Contentmentioning
confidence: 99%